Confirmação matemática do efeito Aharonov-Bohm no modelo sem interação com a fronteira do solenóide - Romano, Renan Gambale (2016)
We study the Aharonov-Bohm effect model by adding a scalar potential in the initial Hamiltonian. Using known techniques of quantum confinement, we show that under certain conditions of divergence on this potential, the family of self-adjoint extensions is reduced to a single operator, which would then be the Schrödinger operator for this situation. The lack of boundary conditions to define this operator is interpreted as no particle interaction with the boundary of the solenoid. We checked the possible manifestation of the Aharonov-Bohm effect in this model without interaction with the solenoid border by studying the dependence of the first eigenvalue associated with the Schrödinger operator with respect to a parameter directly related to the magnetic flux by the solenoid. We have shown that this dependence is non-trivial and periodic, which strictly confirms the Aharonov-Bohm effect for this situation. We also study some particular cases whose explicit solution can be achieved, the solenoid with zero radius in a limited and unlimited region of the plane.